2021
DOI: 10.1063/5.0037192
|View full text |Cite
|
Sign up to set email alerts
|

High responsivity InGaAsSb p–n photodetector for extended SWIR detection

Abstract: A molecular beam epitaxy-grown InGaAsSb p–n photodetector lattice matched to GaSb for extended short wave infrared is reported. Electrical and optical characteristics were analyzed at temperatures from 200 K to room temperature. The photodetectors exhibit dark current densities of 2.9 × 10−6 A/cm2 at 200 K and 4.6 mA/cm2 at 300 K (−0.1 V bias) and a high quantum efficiency of 73% at room temperature under front side illumination. High detectivity (D*) values of 2.2 × 1010 cm·Hz1/2 W−1 and 7.4 × 1011 cm·Hz1/2 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Perimeter/area dependence evaluation suggested that the photodiode was not bulk limited, therefore the full capability of these photodiodes has not yet been reached. Shafir et al 20 has reported diffusion limited current in a homojunction p-n InGaAsSb photodiode at room temperature, showing that diffusion limited current in the material is possible. The leakage current limitations in this work could be overcome with improved material growth.…”
Section: Optical and Electrical Characterizationmentioning
confidence: 99%
“…Perimeter/area dependence evaluation suggested that the photodiode was not bulk limited, therefore the full capability of these photodiodes has not yet been reached. Shafir et al 20 has reported diffusion limited current in a homojunction p-n InGaAsSb photodiode at room temperature, showing that diffusion limited current in the material is possible. The leakage current limitations in this work could be overcome with improved material growth.…”
Section: Optical and Electrical Characterizationmentioning
confidence: 99%
“…Nevertheless, the overall performance of these devices is not yet satisfactory for applications at room temperature. The quaternary material InGaAsSb lattice-matched to GaSb can provide photodetectors operating at room temperature in a wavelength range beyond 1.7 μm [6][7][8][9][10] . For the development of a thermographic traffic-monitoring system that is supposed to increase safety on road and rail by localizing potentially dangerous overheated hot-spot regions, an uncooled InGaAsSb-based detector line array for imaging in the eSWIR is under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Furthermore, a severe reduction of QE in extended InGaAs is observed that has been attributed to the relatively large band offsets present in heterojunction architectures that are usually employed to reduce Shockley-Read-Hall (SRH) junction dark current. [19][20][21][22] While HgCdTe SWIR photodetectors have shown remarkable performance levels, the reported devices appear to be based on MWIR device designs in which the absorber composition has been tailored to the desired SWIR cut-off wavelength. Although HgCdTe devices do not face the challenge of strain-engineering, they also typically require cooling to 200 K or below.…”
Section: Introductionmentioning
confidence: 99%